Identification of Physical Process of RoFI (Region of Freshwater Influenced) at Banyuasin Estuary, South Sumatera of Indonesia - Muh. Adhim Adrian; I Wayan Nurjaya; Dietriech Geoffrey Bengen; Jonson Lumban Gaol; Heron Surbakti (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research The large river discharge from several tributaries causes strong stratification in the Banyuasin Estuary. RoFI in the Banyuasin Estuary does not only occur seasonally, but can also occur in daily cycles. Tidal dynamics control RoFI dynamics in the Banyuasin Estuary. Estuarine plumes formed on the surface based on synoptic imagery prove that RoFI can also extend seasonally.   Abstract The Region of Freshwater Influence (RoFI) is the river-sea transition zone where freshwater, suspended materials, and associated properties are exchanged and redistributed by estuarine dynamics. This study is the first to identify RoFI and contributes to increasing primary productivity in aquatic environments. This research aims to identify physical processes such as tides and currents in the RoFI based on observational CTD data. CTD measurements (14 stations) collected data salinity, temperature, density, and turbidity, visualized using ODV. Tidal and current data identified RoFI dynamic controls. Sentinel-2A imagery mapped the surface plume. RoFI dynamics exhibit significant seasonal and daily changes. Low salinity 10–15 PSU, indicating freshwater intrusion, dominates, with residual currents typically ranging from 0.1 m/s to 0.2 m/s. PCA analysis 91.32% variability demonstrates that the RoFI expands during ebb tide and narrows during flood tide due to estuarine intrusion of high-salinity oceanic currents. RoFI in the Banyuasin estuary introduce freshwater, nutrients, suspended particulates, and even pollutants that can cause large-scale detriment. Therefore, the recommendations given are that the protection of spawning and nursery areas, as well as the control of aquaculture waste, should be prioritized to minimize pressure on fishery resources.